Nature (as) Language in the Poetry of Seán Lysaght - Pietrzak, Wit (Hungarian Journal of English and American Studies, 2021)
The article focuses on a selection of poems by the Irish poet Seán Lysaght to demonstrate that in his work, Lysaght looks to explore nature’s intricate design, its pre-human and pre-linguistic layers of significance through investigations of birds, arguing that rather than offering culturally or politically inflected images of wildlife and landscape, as Irish poets from W. B. Yeats through Patrick Kavanagh all the way to Seamus Heaney and Michael Longley have been wont to do, Lysaght sets the vast natural world, which eludes apprehension in language, against the modern world and its obsession with material productivity and pragmatic efficiency. This aspect of Lysaght’s poetry is discussed against the background of Heaney, Yeats, and William Wordsworth, who are shown to share some insights with Lysaght, but from whose influence he strives to steer away. (WP)